Non-alcoholic fatty liver disease and subclinical atherosclerosis: A comparison of metabolically- versus genetically-driven excess fat hepatic storage. (February 2017) - Di Costanzo, Alessia; D'Erasmo, Laura; Polimeni, Licia; Baratta, Francesco; Coletta, Paola; Di Martino, Michele; Loffredo, Lorenzo; Perri, Ludovica; Ceci, Fabrizio; Montali, Anna; Girelli, Gabriella; De Masi, Bruna; et al.
Abstract: Background and aims: Non-alcoholic fatty liver disease (NAFLD) is frequently associated with atherosclerosis. However, it is unclear whether this association is related to excess fat liver storage per se or to metabolic abnormalities that typically accompany NAFLD. To investigate this, we compared individuals with hepatic steatosis driven by metabolic disturbances to those with hepatic steatosis associated with the rs738409 GG genotype in the patatin-like phospholipase domain-containing 3 gene ( PNPLA3 ). Methods: Carotid intima-media thickness (CIMT), as a surrogate marker of subclinical atherosclerosis, was measured in 83 blood donors with the mutant GG genotype (group G), 100 patients with features of metabolic syndrome (MetS) but the wildtype CC genotype (group M), and 74 blood donors with the wildtype CC genotype (controls). Fatty liver was evaluated by ultrasonography and hepatic fat fraction (HFF) was measured using magnetic resonance (MRS/MRI) in 157 subjects. Results: Compared with group G and controls, group M subjects were older and had increased adiposity indices, dyslipidemia, insulin resistance and elevated transaminase levels (all p  < 0.05). They also had a more fatty liver on both ultrasonography and MRS/MRI. After adjustment for confounders (including severity of hepatic steatosis), the median CIMT in group M (0.84 [0.70–0.95] mm) was significantly greater than that in group G (0.66 [0.55–0.74] mm; p  < 0.001), which was similar to that in controls (0.70 [0.64–0.81] mm). Results were similar in the subgroup evaluated using MRS/MRI. Conclusions: Excess liver fat accumulation appeared to increase the burden of subclinical atherosclerosis only when it is associated with metabolic abnormalities. Highlights: The role that excess hepatic fat (steatosis) plays in atherosclerosis is unclear. CIMT is higher in metabolically-vs genetically-driven liver steatosis. Hepatic fat content per se does not appear a risk factor for atherosclerosis.